2020
DOI: 10.1029/2019av000133
|View full text |Cite
|
Sign up to set email alerts
|

Citizen Scientists Discover a New Auroral Form: Dunes Provide Insight Into the Upper Atmosphere

Abstract: Auroral forms are like fingerprints linking optical features to physical phenomena in the near-Earth space. While discovering new forms is rare, recently, scientists reported of citizens' observations of STEVE, a pinkish optical manifestation of subauroral ionospheric drifts that were not thought to be visible to the naked eye. Here, we present a new auroral form named "the dunes". On 7 October 2018, citizen observers took multiple digital photographs of the same dunes simultaneously from different locations i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
29
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 41 publications
(52 reference statements)
4
29
0
Order By: Relevance
“…One such example is airglow, which can produce the same 557.7 nm and 630.0 nm emission lines of atomic oxygen as typical aurorae, but in this case it is due to dissociative electron recombination (e.g. Peverall et al, 2000). Interaction between aurorae and the dynamics of the neutral atmosphere is a complex subject, with features such as the recently discovered dunes potentially being caused by atmospheric wave modulation on diffuse aurorae (Palmroth et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One such example is airglow, which can produce the same 557.7 nm and 630.0 nm emission lines of atomic oxygen as typical aurorae, but in this case it is due to dissociative electron recombination (e.g. Peverall et al, 2000). Interaction between aurorae and the dynamics of the neutral atmosphere is a complex subject, with features such as the recently discovered dunes potentially being caused by atmospheric wave modulation on diffuse aurorae (Palmroth et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Peverall et al, 2000). Interaction between aurorae and the dynamics of the neutral atmosphere is a complex subject, with features such as the recently discovered dunes potentially being caused by atmospheric wave modulation on diffuse aurorae (Palmroth et al, 2019). Thus, not all emissions similar to aurorae are caused by particle precipitation; Strong Thermal Emission Velocity Enhancement (STEVE) is already a well-known example of aurora-like skyglow which is likely caused by local acceleration processes instead of precipitation (Gallardo-Lacourt et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…These simulations can be used to assess the electric and magnetic fields within large volumes and map them to the ionospheric plane. In fact, global MHD simulations have shown that the Poynting flux starts to focus towards the magnetosphere and ionosphere already from the solar wind in regions where the open field lines are dragged towards the tail (Papadopoulos et al, 1999;Palmroth et al, 2003;Palmroth et al, 2006c). Zhang et al (2012) used a global MHD simulation, mapped the Poynting flux in the tail to the ionosphere, and confirmed that its ionospheric distribution reproduced the global morphology of the Poynting flux measured by the Polar satellite.…”
Section: Poynting Fluxmentioning
confidence: 69%
“…The horizontal phase speed of the dunes is also estimated based on the sole analysis of citizen scientist photographs, and it suggests an unusually large propagation speed which might reveal strong neutral winds at the dune altitude. The studied event took place on 20 January 2016 above Northern Europe; this event is part of the list given in the dune aurora seminal paper (Palmroth, Grandin, Helin, et al, 2020).…”
mentioning
confidence: 99%